Pediatric Patient and Family Advisory Councils: A Guide to Their Development and Ongoing Implementation. (December 2020) - Richard, Julie; Azar, Rima; Doucet, Shelley; Luke, Alison
Background: Patient and family engagement is increasingly recognized in the care of children with complex health conditions. Through the implementation of Patient and Family Advisory Councils (PFACs), health-care institutions are working to improve patient care by nurturing partnerships among patients/families, managers, and clinicians. Despite the potential for PFACs, empirical research about their implementation remains scarce. Objective: To address this gap, this study explored the recruitment, retention, and implementation strategies used by Canadian PFACs. Design: We used a qualitative descriptive design. Participants: We interviewed 10 spokespersons from Canadian PFACs. Results: We found themes within 2 stages of implementation. The first stage, getting PFACs started, included 4 themes: (1) using evolving recruitment methods, (2) preparing for effective participation, (3) ensuring diversity within PFACs, and (4) preparing terms of reference. The second stage involved strategies to support ongoing PFACs implementation and included 1 overall theme: facilitating optimal PFACs participation. The underlying link between themes was that establishing/maintaining PFACs is an ongoing learning curve. Conclusion: Our findings have the potential to inform new and existing PFACs.